Uma proposta metodológica para o ensino das funções trigonométricas - Batista, Valéria Nogueira (Universidade Federal de São Carlos, 2015)
This research has focused primarily on teaching trigonometric sine and cosine functions. The proposal is to organize the teaching of these functions, in order to improve good learning situations to students, to encourage the transition of trigonometric ratios in right triangle to the trigonometric circle with the use of manipulative materials and GeoGebra software. Based on the theoretical assumptions described in the High School National Curriculum Standards and Curriculum of the State of São Paulo seeking to outline for the teacher, the skills and expertise that student must acquire to be made in basic education, are presented educational alternatives. It aims to help students understand the need and the practical applicability of Trigonometric Functions. Analyzing how these functions are covered in the curriculum documents and books of the National Textbook Program (PNLD 2015), we tried to develop a pioneering work and research including mathematical modeling and taking as reference the exploratory and investigative activities.
Keywords: Funções trigonométricas; GeoGebra; Modelagem matemática; Tarefas exploratório-investigativas; Materiais manipulativos; Trigonometric functions; Mathematical modeling; Exploratory- investigative tasks; Manipulative materials; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA